2004
DOI: 10.1016/j.femsle.2004.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Promoted proliferation of an SOD-deficient mutant of Escherichia coli under oxidative stress induced by photoexcited TiO2

Abstract: An SOD null mutant of Escherichia coli (IM303) and its wild-type strain (MM294) were cultivated with or without sublethal oxidative stress generated from photoexcited TiO2. Concerning maximum specific growth rate of the cells, mum, measured under various conditions, the mum value of IM303 cells increased notably in the presence of TiO2 illuminated with light (I = 12.5 W m(-2)), being about two times higher than that of the cells grown in the absence of TiO2 and light. The mum value of IM303 cells under the oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…In our previous study (Kim et al 2004), it was found that SOD-deficient E. coli cells suffering sublethal oxidative stress from photoexcited titanium dioxide (TiO 2 ) unexpectedly exhibited stimulated growth and decreased ROS content in the cells, suggesting that some changes of metabolic patterns occur to cope with the stress. In the present work, the SOD-deficient cells were cultivated under the conditions with and without photoexcited TiO 2 , and physiological responses were compared in terms of mRNA expressions and activities of enzymes in acetic acid-producing pathway and TCA cycle, to understand a strategy of the cells for surviving under the oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study (Kim et al 2004), it was found that SOD-deficient E. coli cells suffering sublethal oxidative stress from photoexcited titanium dioxide (TiO 2 ) unexpectedly exhibited stimulated growth and decreased ROS content in the cells, suggesting that some changes of metabolic patterns occur to cope with the stress. In the present work, the SOD-deficient cells were cultivated under the conditions with and without photoexcited TiO 2 , and physiological responses were compared in terms of mRNA expressions and activities of enzymes in acetic acid-producing pathway and TCA cycle, to understand a strategy of the cells for surviving under the oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work (12), it was reported that the population of SOD-deficient mutant of E. coli IM303 contained a trace of spontaneously derived variant cells which prevailed during the culture under the oxidative stress generated by photoexcited titanium dioxide (TiO 2 ). This result suggested that the variant cells possibly acquired a certain defense system against the oxidative stress besides the SOD mechanism.…”
mentioning
confidence: 99%
“…Strain IM303 (I4) was one of isolates obtained from an original population of the mutant (12 (21). RNA extraction was conducted as follows, using IM303 (I4) cultures with and without the oxidative stress generated by light-irradiated TiO 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations